AB0025 Is Abatacept Successful in Improving Insulin Resistance in A High Fat Diet Model of Obesity?. (10th June 2014) - Mauro, D.; Ursini, F.; Naty, S.; Bruno, C.; Calabria, M.; Tripolino, C.; Grembiale, R.D.; Hribal, M.L.
Abstract : Background: We previously reported a case of improvement in insulin resistance (IR) in a Rheumatoid Arthritis (RA) patient treated with the fusion protein Abatacept (CTLA-4Ig), selectively designed to modulate the immune cells co-stimulatory signal mediated through the CD28-CD80/86 pathway. To current evidences the blunting of this pathway in AT could, at least in theory, partially restore the altered ratio between activated CD8+ effector T cells and CD4+ lymphocytes, as well as reduce the pro-inflammatory macrophage phenotype observed in early IR in obese mice and in humans affected by T2DM. Objectives: The aim of the present study was to investigate whether Abatacept may be able to redue insulin resistance in an experimental model of high fat diet induced obesity. Methods: Twenty C57BL6J mice (HFD mice) were fed a High Fat Diet (60% Kcal from fat) obtained from Research Diets (NY, USA, diet D12492) for 3 months starting at weaning; 18 age- and weight-matched littermates were fed with normal chow as a control group. After 3 months, mice were weighted and subjected to intraperitoneal glucose tolerance tests (IPGTT). HFD mice were than subdivided in two groups: a) the first group (ABA) was treated with Abatacept (20 mg/kg. I.P.) according to the following schedule: 1st injection at 3 months of age, 2nd injection after 15 days, 3rd injection after 15 days (1 month from the 1st injection) followed by the 4th, 5th and 6th injections, each after 1 month from the other (2, 3, 4 months respectively from the first injection; b) the second group (SAL) was injected with saline at corresponding time points. Body weight and glycaemia were assessed every 15 days and, finally, saline and Abatacept-treated mice were subjected to IPGTT. Results: HFD mice weight was significantly higher than in control mice (mean values 45±8 g vs 32±6; respectively, p<0.05) and HFD mice developed glucose intolerance. No differences in body weight and glycaemia were observed between ABA and SAL mice during the study (mean weight after 3 months on HFD: 55±7 g in ABA mice vs 53±6 in SAL mice; glucose levels after 3 months of HFD: 203±7 ABA mice vs 198±12 in SAL mice). The IPGTT performed at the end of the study showed that glucose tolerance significantly worsened in both Abatacept and saline treatment groups as a consequence of the additional four months of HFD. Therefore, no protective effect of Abatacept could be detected. Conclusions: Abatacept appears per se to be ineffective to improve insulin resistance in a mouse model of diet induced obesity without inflammatory diseases. The discrepancy with what previously observed in RA patients highlights the contribution of autoimmunity and inflammation to IR genesis during the course of rheumatic diseases. References: L. Bird, Inflammation: Finding the T in fat, Nat. Rev. Immunol., vol. 9, no. 9, pp. 607–607, Aug. 2009. F. Ursini, D. Mauro, S. Naty, D. Gagliardi, and R. D. Grembiale, Improvement in insulin resistance after short-term treatment with abatacept: case report and short review, Clinical Rheumatology, vol. 31. pp. 1401–1402, 2012. S. Nishimura, I. Manabe, and R. Nagai, Adipose tissue inflammation in obesity and metabolic syndrome, Discov. Med., vol. 8, no. 41, pp. 55–60, Aug. 2009. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.2775